(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the creation of a database of tasks and an electronic dictionary for the formation of concepts of conflict in the minds of elementary school students and its impact on students. It is planned to improve the teaching of the Uzbek language to elementary school students by creating modern, new-generation educational dictionaries and their electronic forms and a dictionary of terms by fields.